Room Temperature Direct Band Gap Emission from Ge p-i-n Heterojunction Photodiodes. (28th February 2012) - Kasper, E.; Oehme, M.; Arguirov, T.; Werner, J.; Kittler, M.; Schulze, J.
Abstract : Room temperature direct band gap emission is observed for Si-substrate-based Ge p-i-n heterojunction photodiode structures operated under forward bias. Comparisons of electroluminescence with photoluminescence spectra allow separating emission from intrinsic Ge (0.8 eV) and highly doped Ge (0.73 eV). Electroluminescence stems from carrier injection into the intrinsic layer, whereas photoluminescence originates from the highly n-doped top layer because the exciting visible laser wavelength is strongly absorbed in Ge. High doping levels led to an apparent band gap narrowing from carrier-impurity interaction. The emission shifts to higher wavelengths with increasing current level which is explained by device heating. The heterostructure layer sequence and the light emitting device are similar to earlier presented photodetectors. This is an important aspect for monolithic integration of silicon microelectronics and silicon photonics.